Discovering the Unexpected with the Utilization of NGS in Diagnostics of Non-syndromic Hearing Loss Disorders: The Family Case of ILDR1-Dependent Hearing Loss Disorder - Kovač, Jernej; Klančar, Gašper; Trebušak Podkrajšek, Katarina; Battelino, Saba (Frontiers in Genetics, 2017)
Sensorineural hearing loss (SNHL) is a heterogeneous family of hearing disabilities with congenital (including genetic) as well as acquired etiology. Congenital SNHL of genetic etiology is further sub-divided into autosomal dominant, autosomal recessive and X-linked SNHL. More than 60 genes are involved in the etiology of autosomal recessive non-syndromic hearing loss (ARNSHL) commonly manifesting as heterogeneous pre-lingual profound to severe non-progressive clinical phenotype. ILDR1-dependent ARNSHL (DFNB42, OMIM: # 609646) is a very rare sub-type of hearing disability, with unknown prevalence, caused by function-damaging genetic variants in ILDR1 gene reported in families of Middle-Eastern origin. ILDR1 (Immunoglobulin-Like Domain-containing Receptor 1) is involved in the development of semicircular canal, tricellular tight junction and auditory hair cells. An apparently non-consanguineous family of European ancestry with two affected siblings with profound progressive hearing loss characterized in their infancy and successfully treated with cochlear implants (CI) is presented. Genetic analysis of common ARNSHL genetic causes in the population of origin was negative, thus the next-generation sequencing (NGS) and family segregation analysis to identify underlying causative genetic variant was performed. Unexpectedly and atypical for the population of origin a homozygous non-sense variant ILDR1 c.942C>A (p.Cys314Ter) inherited from both heterozygous parents was identified in both probands. Contrary to the commonly reported phenotype, indices of a progressive hearing loss and potential compensatory mechanism of vestibular function were revealed with the analysis of clinical data. The utilization of NGS was demonstrated as an invaluable tool for the detection of atypical rare variants in diagnostics of unidentified hearing loss disorders.